Penggunaan Air Kelapa dan Indol-3-Butyric-Acid Iba Untuk Induksi Multiplikasi Tunas Eksplan Tanaman Kentang (Solanum Tuberosum L.) Secara In-Vitro - Novi Septiawati; Syahbudin Hasibuan; Rizal Aziz (Universitas Medan Area, 2021)
This study aims to obtain the concentration and IBA the best formation and growth in potato plants (Solanum tuberosum L)implemented since months july 2019 - October 2019 in the Tissue Culture LaboratoryGrowth CentreLembaga Layanan Pendidikan Tinggi Wilayah I Jalan Pratun No. 1Medan Estate .The design used in this study isCompletely Randomized Design (CRD) consisting of 1 factor treatment namely A1 = control (without coconut water); A2 = 10 ml/l; A3 = 20 ml/l; A4= 30 ml/l, B0 = Positive control (Benzyl Amino Purine) 3 mg/l; B1 = 1 mg/l; B2 = 3 mg/l; B3 = 5 mg/l, each treatement was repeated 2 times . beside that, the parameter observed was the number of shoots, number of leaves, plant height, early appear roots, number of roots and root length. From the results of this study, the following conclusions can be drawn : 1) giving coconut water explants and IBA had no real effect on number of shoots,number of leaves , plant height, early emergence of roots, number of roots and root legenth.in this case the provision of coconut water 10 ml/l (A2) ,can stimulate the formation of the roots faster (7,63 day) the number of roots more (23,63 pieces) and the roots are longer (5,91 cm) while giving IBA concentration 1mg/l (B1) can increase the number of leaves by as much 29,88sheet.